ANALISIS RASIO KEUANGAN DALAM MENILAI KINERJA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fatasya, Sykin; Natalia, Erni Yanti (SCIENTIA JOURNAL, 2022)
The purposes of researches means to analyze impact of Currents Ratios also Debts Equity Ratios on Returnon Equity in manufacture company list on Indonesia Stocks Exchanges for periods 2016 -2019. In generatingcompany's profit level, one indicatoring used is Returned on Equity. The research use an associativequantitatives approachs. The population were 30companies. The sample use is 14companies use purposivesampling methods. Secondary data as a data collection technique using descriptives analysis in the form ofannual financiasl report for year 2016 till 2019 periods. Results of the study explain is partiallies CurrentRatios has no impact of Returns on Equity as indicates by significances values of0.066. Debt Equity Ratioshas an impact on Returns on Equity indicate by significances valueable of0.002. Simultaneouslly CurrentRatio also Debts Equity Ratios has a significances impact of Returns on Equity. The coefficient ofdetermination of 14.9% mean that Currents Ratios also Debts Equity Ratio variable may explains of Returnson Equity variables also remainings 85.1% is explain by others variable not explained on this researches.